2022
DOI: 10.1590/0102-311xen013122
|View full text |Cite
|
Sign up to set email alerts
|

Urgent dental care in the Brazilian public health system: learning lessons from the COVID-19 pandemic for future situations

Abstract: This ecological study described the effect of the COVID-19 pandemic and socioeconomic development on the use and profile of urgent dental care (UDC). UDC rates per 100,000 inhabitants before (from March to June 2019) and during (from March to June 2020) the COVID-19 pandemic in 4,062 Brazilian municipalities were compared. Data were collected from official sources. COVID-19 mortality and hospitalization rates were indicative of levels of lockdown and Human Development Index (HDI) indicated socioeconomic develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…In 2021, the probability of oral health services utilization by Peruvian children under 12 years of age decreased by 45% compared to 2017. A similar trend of reduced oral health services utilization has been identified in some ecological studies, encompassing the majority of municipalities in Brazil as well [ 33 , 34 ]. This problem could be due to the fact that during the COVID-19 pandemic the World Health Organization issued a series of recommendations to reduce the application of aerosol-generating procedures in the context of oral health care as a measure to prevent the spread of the virus [ 35 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In 2021, the probability of oral health services utilization by Peruvian children under 12 years of age decreased by 45% compared to 2017. A similar trend of reduced oral health services utilization has been identified in some ecological studies, encompassing the majority of municipalities in Brazil as well [ 33 , 34 ]. This problem could be due to the fact that during the COVID-19 pandemic the World Health Organization issued a series of recommendations to reduce the application of aerosol-generating procedures in the context of oral health care as a measure to prevent the spread of the virus [ 35 ].…”
Section: Discussionsupporting
confidence: 75%
“…Nonetheless, we hypothesize that individuals with higher socioeconomic status may have sought oral health services less frequently for preventive or cosmetic purposes, while those with lower socioeconomic standing, who may have poorer overall health, may have sought dental care due to genuine emergencies or urgent needs more frequently. Indeed, another study conducted in Brazil, reported greater reductions in urgent dental care during the most stringent period of the pandemic in municipalities with higher human development indices compared to 2019 [ 34 ]. In the Peruvian context, the pandemic scenario could have created a temporary and deceptive reduction in inequalities in oral health services utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, comparing the months of March to June 2019 and 2020, municipalities with a higher Human Development Index and greater coverage of PHC presented a lower reduction in emergency appointments at this level of care [ 32 ]. Therefore, it can be considered that living conditions and service structuring in the study’s scenario may have helped children access emergency treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Other care would be the responsibility of primary care. 23 In this way, primary care professionals-including family health units and basic health units-are responsible for providing emergency care in cases where there is a potential for the situation to worsen, but which do not pose a risk of death or where it may lead to the limitation of the individual's usual activities. 24 As such, the following are considered emergency care acute odontogenic pain; pericoronaritis or pain related to infectious processes involving the retained third molars; alveolitis; dental or periodontal abscesses or bacterial infection, resulting in localized pain and edema; dental fracture resulting in pain or trauma to oral soft tissues; cementation of crowns or fixed prostheses; biopsies; adjustments of orthoses and prostheses that are causing pain and compromising masticatory function; opening or changing intracanal medication; removal of extensive caries lesions/restorations that are causing pain; treatment of tissue necrosis with pain and presence of purulent secretion; mucositis; dental trauma with avulsion or luxation.…”
Section: Discussionmentioning
confidence: 99%
“…Extended elective services, on the other hand, are those which, if postponed, do not cause great harm to the user. 23 The federal council of dentistry (CFO) states that nonemergency dental procedures include the restoration of teeth, including the treatment of asymptomatic carious lesions, and dental procedures for aesthetic purposes. 26 Elective surgeries, tooth extraction and asymptomatic periodontal surgeries, implant dentistry, orthognathic surgeries and other surgeries that are not listed under urgencies and emergencies are procedures in which care can be scheduled without risk to the user's health.…”
Section: Discussionmentioning
confidence: 99%